Cathode powder and preparation method and application thereof
The SOFC cathode powder precursor solution is processed through ultrasonic atomization and thermal decomposition technology and coated in the sintering step, which solves the problems of uneven particle size distribution and low catalytic activity of the cathode powder in the prior art, and achieves efficient and low-cost cathode powder preparation, which improves the conductivity and catalytic activity.
Patent Information
- Application Number
- CN202510028133.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The existing SOFC cathode powder preparation methods have problems such as uneven particle size distribution, low catalytic activity, low production efficiency and high cost.
Ultrasonic atomization and thermal decomposition technology were used to process perovskite-like and spinel-like precursor solutions respectively to form a xylogel. Then, buffer and spinel-like digel were coated in the sintering step to prepare cathode powder with excellent conductivity and catalytic activity.
The particle size uniformity, conductivity, surface exchange coefficient and bulk phase oxidation diffusion coefficient of the cathode powder are improved, the polarization impedance is reduced, and the conductivity, catalytic activity and reaction activity are improved.
Smart Images

Figure BDA0005233366520000111 
Figure BDA0005233366520000121 
Figure BDA0005233366520000131
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid oxide fuel cells, and in particular relates to a cathode powder and a preparation method and application thereof. Background Art
[0002] The existing cathode powder for SOFC (solid oxide fuel cell) needs to go through the steps of powder mixing, precursor solution preparation, high temperature calcination of powder and powder ball milling / sand milling during preparation. The particle size distribution, particle morphology, specific surface area and degree of agglomeration of the powder will affect the electrochemical properties such as polarization impedance and overpotential of the electrode after sintering of the powder. The traditional methods for preparing cathode materials for SOFC mainly include solid phase reaction method, sol-gel method, self-propagating combustion method and other synthesis methods. The synthesis temperature required for the solid phase reaction method to synthesize powder materials is high, the preparation cycle required for the ball milling process is long, and the particle size of the synthesized powder is too large, resulting in low catalytic activity of the powder. The materials prepared by the sol-gel method and the self-propagating combustion synthesis method have uniform components, fast reaction rate, low energy consumption required for the reaction, and high catalytic activity of the synthesized powder, but the synthesis process is cumbersome, the yield of the powder is low, and the pollutants discharged during the synthesis process are too much. Summary of the invention
[0003] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a method for preparing cathode powder.
[0004] A second object of the present invention is to provide a cathode powder.
[0005] A third object of the present invention is to provide a solid oxide fuel cell.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A first aspect of the present invention provides a method for preparing a cathode powder, comprising the following steps:
[0008] Step 1: homogenizing, ultrasonically atomizing, and drying the mixed solution 1 and the mixed solution 2 in sequence to obtain a mixed aerosol 1 and a mixed aerosol 2;
[0009] Step 2: thermally decomposing the mixed aerosol 1 and the mixed aerosol 2 to obtain a perovskite-like xerogel and a spinel-like xerogel, respectively;
[0010] Step 3: sequentially coating the surface of the perovskite-like dry gel with a buffer and a spinel-like dry gel, and then sintering to obtain the cathode powder;
[0011] The first mixed solution contains a perovskite-like precursor; the second mixed solution contains a spinel-like precursor;
[0012] The molar ratio of the perovskite-like dry gel to the spinel-like dry gel is 1:(4.5-6.5).
[0013] In some embodiments of the present invention, the ultrasonic frequency in the ultrasonic atomization step is 1.5 to 2 Hz.
[0014] In some embodiments of the present invention, the nebulization rate in the ultrasonic nebulization step is 1 to 2 mL / min.
[0015] In some embodiments of the present invention, the thermal decomposition temperature of the mixed aerosol is 1200-1400°C.
[0016] In some embodiments of the present invention, the thermal decomposition time of the mixed aerosol is 80-100 min.
[0017] In some embodiments of the present invention, the thermal decomposition temperature of the mixed aerosol 2 is 1000-1200°C.
[0018] In some embodiments of the present invention, the thermal decomposition time of the mixed aerosol 2 is 110-160 min.
[0019] In some embodiments of the present invention, the time required for coating the buffer on the surface of the perovskite-like xerogel is not less than 30 minutes.
[0020] In some embodiments of the present invention, the heating rate of the sintering step is 5-10° C. / min.
[0021] In some embodiments of the present invention, the sintering temperature of the sintering step is 400-600°C.
[0022] In some embodiments of the present invention, the holding time of the sintering step is 3 to 4 hours.
[0023] In some embodiments of the present invention, the drying temperature is 100-200°C.
[0024] In some embodiments of the present invention, the drying time is 30-40 minutes.
[0025] In some embodiments of the present invention, the pressure of the homogenization step is 200-250 MPa.
[0026] In some embodiments of the present invention, the temperature of the homogenization step is 30-40°C.
[0027] In some embodiments of the present invention, step 3 is: passing a gas containing a buffer into a gas containing a perovskite-like dry gel so that the buffer is coated on the surface of the perovskite-like dry gel; then passing a gas containing a spinel-like dry gel, and then sintering.
[0028] In some embodiments of the invention, the flow rate of the buffer-containing gas is <20 mL / min.
[0029] In some embodiments of the present invention, the flow rate of the gas containing the spinel-like xerogel is <20 mL / min.
[0030] In some embodiments of the present invention, the perovskite-like n+1 B n O 3n+1 ; n is an integer of 1 to 4; A is selected from rare earth metals; B is selected from transition metals.
[0031] In some embodiments of the present invention, the spinel-like material is CD2O4; C and D are both transition metals.
[0032] In some embodiments of the present invention, the buffer is selected from at least one of NH3·H2O and NH4HCO3.
[0033] In some embodiments of the present invention, the mixed solution 1 further contains a complexing agent and a pH regulator, and the molar ratio of perovskite precursor: complexing agent: pH regulator is 1: (1-1.2): (1.3-1.7).
[0034] In some embodiments of the present invention, the second mixed solution further contains a precipitant, and the molar ratio of the spinel-like precursor to the precipitant is 1:(1-1.5).
[0035] In some embodiments of the present invention, the molar ratio of the perovskite-like xerogel to the buffer is (3.2-4):1.
[0036] In some embodiments of the present invention, the pH of the mixed solution 1 and / or the mixed solution 2 is 7.5-8.
[0037] In some embodiments of the present invention, the mixed solution 1 and the mixed solution 2 are subjected to step 1 and step 2 simultaneously.
[0038] The second aspect of the present invention provides a cathode powder, which is prepared by the preparation method described in the first aspect of the present invention; the cathode powder contains spinel-like and perovskite-like; the spinel-like is coated on the surface of the perovskite-like.
[0039] In some embodiments of the present invention, the specific surface area of the cathode powder is 4 to 8 m 2 / g.
[0040] In some embodiments of the present invention, the cathode powder D 50 The particle size is 0.62-0.74μm.
[0041] In some embodiments of the present invention, the cathode powder D 90 The particle size is 1.3-1.6μm.
[0042] In some embodiments of the present invention, the conductivity of the cathode powder is greater than 5 S / cm.
[0043] In some embodiments of the present invention, the polarization impedance value of the cathode powder measured at 780°C is less than 0.96Ω·cm 2 .
[0044] In some embodiments of the present invention, the surface exchange coefficient of the cathode powder measured at 700°C is 7.11×10 -5 ~8.73×10 -5 cm / s.
[0045] In some embodiments of the present invention, the bulk oxygen chemical diffusion coefficient of the cathode powder measured at 600°C is 1.61×10 -3 ~2.13×10 -3 cm / s.
[0046] The third aspect of the present invention provides a solid oxide fuel cell, comprising a cathode, wherein the cathode contains the cathode powder described in the first aspect of the present invention.
[0047] The beneficial effects of the present invention are as follows: the preparation method of the present invention can greatly improve production efficiency, reduce production costs, simplify preparation steps, and improve the yield of cathode powder by homogenizing, ultrasonically atomizing, drying and thermally decomposing the mixed liquid one and the mixed liquid two respectively, so that the cathode powder has excellent particle size uniformity, improves the electrical conductivity, surface exchange coefficient, and bulk oxygen chemical diffusion coefficient of the cathode powder, and reduces the polarization impedance of the cathode powder, thereby making the cathode powder have excellent electrical conductivity, catalytic activity and reaction activity.
[0048] The cathode powder in the present invention has excellent electron and ion transport properties, and the cathode powder has a stable structure and has properties such as a low thermal expansion coefficient, a high diffusion coefficient, a strong oxygen exchange capacity and a surface adsorption force. DETAILED DESCRIPTION
[0049] The specific implementation of the present invention is further described in detail below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.
[0050] In some embodiments of the present invention, the present invention provides a method for preparing a cathode powder, comprising the following steps:
[0051] Step 1: homogenizing, ultrasonically atomizing, and drying the mixed solution 1 and the mixed solution 2 in sequence to obtain a mixed aerosol 1 and a mixed aerosol 2;
[0052] Step 2: thermally decomposing the mixed aerosol 1 and the mixed aerosol 2 to obtain a perovskite-like xerogel and a spinel-like xerogel, respectively;
[0053] Step 3: sequentially coating the surface of the perovskite-like dry gel with a buffer and a spinel-like dry gel, and then sintering to obtain the cathode powder;
[0054] The first mixed solution contains a perovskite-like precursor; the second mixed solution contains a spinel-like precursor;
[0055] The molar ratio of the perovskite-like dry gel to the spinel-like dry gel is 1:(4.5-6.5).
[0056] In some embodiments of the present invention, the mixed solution 1 and the mixed solution 2 are synchronously carried out in step 1 and step 2; in some embodiments of the present invention, the mixed solution 1 and the mixed solution 2 are synchronously carried out in step 1 and step 2 using a dual-channel synthesis device. The synchronous carrying out of step 1 and step 2 by the mixed solution 1 and the mixed solution 2 can greatly simplify the reaction steps, improve the reaction efficiency, shorten the reaction time, and improve the yield of the cathode powder.
[0057] The present invention adopts dual channels to perform homogenization, ultrasonic atomization, drying and thermal decomposition treatment on the mixed solution one and the mixed solution two, thereby forming perovskite-like dry gel and spinel-like dry gel of different particle sizes, activities and purities, so as to make the subsequent coating more uniform.
[0058] In some embodiments of the present invention, the molar ratio of the perovskite-like dry gel to the spinel-like dry gel can be any value among 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9, 1:5.0, 1:5.1, 1:5.2, 1:5.3, 1:5.4, 1:5.5, 1:5.6, 1:5.7, 1:5.8, 1:5.9, 1:6.0, 1:6.1, 1:6.2, 1:6.3, 1:6.4, 1:6.5 or a range formed by any two of them.
[0059] In some embodiments of the present invention, the ultrasonic frequency in the ultrasonic atomization step is 1.5-2 Hz; in some embodiments of the present invention, the ultrasonic frequency in the ultrasonic atomization step can be any value among 1.5 Hz, 1.6 Hz, 1.7 Hz, 1.8 Hz, 1.9 Hz, 2 Hz or a range formed by any two of them.
[0060] In some embodiments of the present invention, the nebulization rate in the ultrasonic nebulization step is 1 to 2 mL / min; in some embodiments of the present invention, the nebulization rate in the ultrasonic nebulization step can be any value of 1 mL / min, 1.1 mL / min, 1.2 mL / min, 1.3 mL / min, 1.4 mL / min, 1.5 mL / min, 1.6 mL / min, 1.7 mL / min, 1.8 mL / min, 1.9 mL / min, 2 mL / min, or a range formed by any two of the values.
[0061] In the ultrasonic atomization step, the present invention utilizes the high-frequency vibration of ultrasonic transducer to generate directional pressure, so that the liquid surface bulges, cavitation occurs around the bulged liquid surface, and the liquid is atomized into small molecule aerosol. In the ultrasonic atomization step, when the ultrasonic frequency is too low or the atomization rate is too high, the mixed liquid 1 and the mixed liquid 2 will be insufficiently atomized, resulting in the perovskite-like dry gel and spinel-like dry gel agglomerates formed after drying and thermal decomposition having a too wide size distribution range and poor concentration, thereby resulting in insufficient coating in step 3; when the ultrasonic frequency is too high, the median particle size of the aerosol is too small and the distribution range is too wide, which affects the processing of the subsequent process and the basic parameters for preparing the cathode powder.
[0062] In some embodiments of the present invention, the thermal decomposition temperature of the mixed aerosol 1 is 1200-1400°C; in some embodiments of the present invention, the thermal decomposition temperature of the mixed aerosol 1 can be 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C, 1310°C, 1320°C, 1330°C, 1340°C, 1350°C, 1360°C, 1370°C, 1380°C, 1390°C, 1400°C, any one of the values or a range formed by any two of them.
[0063] In some embodiments of the present invention, the thermal decomposition time of the mixed aerosol one is 80-100 min; in some embodiments of the present invention, the thermal decomposition time of the mixed aerosol one can be any value among 80 min, 82 min, 84 min, 86 min, 88 min, 90 min, 92 min, 94 min, 96 min, 98 min, 100 min or a range value formed by any two of them.
[0064] In some embodiments of the present invention, the thermal decomposition temperature of the mixed aerosol 2 is 1000-1200°C; in some embodiments of the present invention, the thermal decomposition temperature of the mixed aerosol 2 can be 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, 1110°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C, 1200°C, any one of the values or a range formed by any two of them.
[0065] In some embodiments of the present invention, the thermal decomposition time of the mixed aerosol 2 is 110-160 min; in some embodiments of the present invention, the thermal decomposition time of the mixed aerosol 2 can be any value among 110 min, 115 min, 120 min, 125 min, 130 min, 135 min, 140 min, 145 min, 150 min, 155 min, 160 min or a range value formed by any two of them.
[0066] The above-mentioned thermal decomposition temperature and thermal decomposition time are used in the present invention to facilitate the coating of the spinel-like xerogel on the surface of the perovskite-like xerogel, thereby improving the uniformity of the coating. If the thermal decomposition temperature is too high or the thermal decomposition holding time is too long, excessive ammonia and / or carbon dioxide and / or hydrogen chloride and other gases will be generated by decomposition, which may easily lead to production safety problems such as overheating and overpressure; if the thermal decomposition temperature is too low or the thermal decomposition holding time is too short, insufficient decomposition or the formation of by-products will occur.
[0067] In some embodiments of the present invention, the time required for coating the buffer on the surface of the perovskite dry gel is not less than 30 minutes; in some embodiments of the present invention, the time required for coating the buffer on the surface of the perovskite dry gel is 30 minutes to 120 minutes; in some embodiments of the present invention, the time required for coating the buffer on the surface of the perovskite dry gel can be any value of 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, 110 minutes, 120 minutes or any range formed by two values; in some embodiments of the present invention, the time required for coating the buffer on the surface of the perovskite dry gel is 30 minutes to 60 minutes; in some embodiments of the present invention, the time required for coating the buffer on the surface of the perovskite dry gel is 30 minutes to 40 minutes. Under the coating time in the present invention, the buffer can be completely coated on the surface of the perovskite dry gel. In order to improve production efficiency and reduce production costs, it is better to coat the time of 30 to 40 minutes. If the coating temperature is too high, the buffer will volatilize or thermally decompose, resulting in insufficient coating. If the coating time is too short or the coating temperature is too low, it will also lead to insufficient coating, resulting in the agglomeration of the perovskite dry gel particles in the later stage, affecting the uniformity and consistency of the composition and particle size of the cathode powder; if the coating time is too long, it will affect the production efficiency.
[0068] In some embodiments of the present invention, the heating rate of the sintering step is 5 to 10°C / min; in some embodiments of the present invention, the heating rate of the sintering step can be any value among 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or a range formed by any two of them.
[0069] In some embodiments of the present invention, the sintering temperature of the sintering step is 400-600°C; in some embodiments of the present invention, the sintering temperature of the sintering step can be 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, any one of the values or a range formed by any two of them.
[0070] In some embodiments of the present invention, the holding time of the sintering step is 3 to 4 hours; in some embodiments of the present invention, the holding time of the sintering step can be any value among 3h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h, 4h or a range formed by any two of them.
[0071] In the present invention, the heating rate of the sintering step is too slow, and the spinel precursor cannot be completely crystallized; the heating rate of the sintering step is too fast and the temperature of the sintering step is too high, and the grains grow excessively, affecting the uniformity of the cathode powder; the temperature of the sintering step is too low, and it is impossible to provide sufficient temperature and pressure to ensure that the spinel material grows and crystallizes fully. The holding time of the sintering step is too short, the crystallinity of the cathode powder is poor, and the grain growth is incomplete; the holding time of the sintering step is too long, and the crystallinity of the cathode powder is too high, which is not conducive to the subsequent grinding process, and too much fine powder will be produced, resulting in unreasonable grading of the powder, and the cathode powder sintering bonding force is poor. In addition, part of the cathode powder will also undergo crystal phase transformation, and the catalytic activity of the cathode powder will be reduced accordingly.
[0072] In some embodiments of the present invention, the drying temperature is 100-200°C; in some embodiments of the present invention, the drying temperature may be any value of 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C or a range formed by any two of them.
[0073] In some embodiments of the present invention, the drying time is 30-40 min; in some embodiments of the present invention, the drying time can be any value among 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min, 40 min or a range value formed by any two of them.
[0074] In the present invention, if the drying temperature is too high or the drying time is too long, the perovskite precursor and the spinel precursor will decompose prematurely, produce by-products, and affect the purity of the final product; if the drying temperature is too low or the drying time is too short, free water or low-boiling point solvent will be insufficiently removed.
[0075] In some embodiments of the present invention, the pressure of the homogenization step is 200-250 MPa; in some embodiments of the present invention, the pressure of the homogenization step can be any value among 200 MPa, 210 MPa, 220 MPa, 230 MPa, 240 MPa, 250 MPa or a range formed by any two of them.
[0076] In some embodiments of the present invention, the temperature of the homogenization step is 30-40°C; in some embodiments of the present invention, the temperature of the homogenization step can be any one of 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C or a range formed by any two of them.
[0077] In some embodiments of the present invention, the number of treatments in the homogenization step is 2 to 10 times; in some embodiments of the present invention, the number of treatments in the homogenization step is 2 to 3 times. In some embodiments of the present invention, the number of treatments in the homogenization step can be any value of 2 times, 3 times, 4 times, 5 times, 6 times, 7 times, 8 times, 9 times, 10 times, or a range formed by any two of them.
[0078] In some embodiments of the present invention, step 3 is: passing a gas containing a buffer into a gas containing a perovskite-like dry gel so that the buffer is coated on the surface of the perovskite-like dry gel; then passing a gas containing a spinel-like dry gel, and then sintering. First, the gas containing a buffer is passed into the gas containing the perovskite-like dry gel to keep warm, so that the buffer is fully coated on the surface of the perovskite-like material, and then the gas containing the spinel-like dry gel is passed, and the perovskite-like material is further grown as the nucleation center, so as to be coated on the surface of the perovskite-like material, forming a perovskite-like material coated on the surface of the spinel-like material.
[0079] In some embodiments of the present invention, the flow rate of the buffer-containing gas is <20 mL / min; in some embodiments of the present invention, the flow rate of the buffer-containing gas can be 1 mL / min, 2 mL / min, 3 mL / min, 4 mL / min, 5 mL / min, 6 mL / min, 7 mL / min, 8 mL / min, 9 mL / min, 10 mL / min, 11 mL / min, 12 mL / min, 13 mL / min, 14 mL / min, 15 mL / min, 16 mL / min, 17 mL / min, 18 mL / min, 19 mL / min, 19.9 mL / min, any one of the values or a range formed by any two of them.
[0080] In some embodiments of the present invention, the buffer-containing gas comprises a buffer and an inert gas.
[0081] In some embodiments of the present invention, the flow rate of the gas containing spinel-like dry gel is <20mL / min; in some embodiments of the present invention, the flow rate of the gas containing spinel-like dry gel can be 1mL / min, 2mL / min, 3mL / min, 4mL / min, 5mL / min, 6mL / min, 7mL / min, 8mL / min, 9mL / min, 10mL / min, 11mL / min, 12mL / min, 13mL / min, 14mL / min, 15mL / min, 16mL / min, 17mL / min, 18mL / min, 19mL / min, 19.9mL / min, any one of the values or a range value formed by any two of them.
[0082] If the flow rate of the gas containing the buffer and / or the gas containing the spinel-like xerogel is too large, the airflow disturbance during coating will be too large, which will lead to the enrichment of the xerogel and insufficient precipitation.
[0083] In some embodiments of the present invention, the gas containing the spinel-like xerogel comprises the spinel-like xerogel and an inert gas.
[0084] In some embodiments of the present invention, the inert gas is selected from at least one of nitrogen, argon and xenon.
[0085] In some embodiments of the present invention, the perovskite is A n+1 B n O 3n+1 ; n is an integer of 1 to 4; A is selected from rare earth metals; B is selected from transition metals. A is usually a rare earth metal with a large radius; B is a transition metal with a medium size. In some embodiments of the present invention, in the perovskite, A is selected from at least one of La, Pr, Nd, Sm, and Eu; in some embodiments of the present invention, in the perovskite, B is selected from at least one of Ni, Cu, and Fe.
[0086] In some embodiments of the present invention, the raw material for preparing the perovskite precursor includes metal nitrate or metal sulfate. In some embodiments of the present invention, the raw material for preparing the perovskite precursor can be selected from one of La2(NO3)3·6H2O, La2(SO4)3·8H2O, Pr(NO3)3, Pr2(SO4)3·4H2O, Nd2(SO4)3·2H2O, Nd(NO3)3·6H2O, Sm(NO3)3, Sm2(SO4)3·6H2O, Eu(NO3)3, Eu2(SO4)3·6H2O, Fe3(NO3)2·9H2O, Fe2(SO4)3·6H2O, Cu(NO3)2·6H2O, CuSO4·5H2O, Ni(NO3)2·6H2O, NiSO4·6H2O, and NiCl6.
[0087] In some embodiments of the present invention, n is an integer of 1 to 4; in some embodiments of the present invention, n can be any value of 1, 2, 3, 4 or a range formed by any two of them.
[0088] In some embodiments of the present invention, the perovskite-like material is La3Fe2O7.
[0089] In some embodiments of the present invention, the spinel-like material is CD2O4; C and D are both transition metals.
[0090] In some embodiments of the present invention, C and D are independently selected from at least one of Mn, Zn, Fe, Co, Cd, Ga, and Ni.
[0091] In some embodiments of the present invention, the spinel-like material is MnCo2O4.
[0092] In some embodiments of the present invention, the raw material for preparing the spinel-like precursor includes at least one of metal nitrates and metal sulfates.
[0093] In some embodiments of the present invention, the raw materials for preparing the spinel-like precursor are selected from at least one of Mn(NO3)2·6H2O, MnSO4·6H2O, Zn(NO3)2·6H2O, ZnSO4·6H2O, Fe3(NO3)2·9H2O, Fe2(SO4)3·6H2O, Co(NO3)2·6H2O, CoSO4·5H2O, Cd(NO3)2·6H2O, CdSO4·6H2O, Ga(NO3)2·6H2O, GaSO4·6H2O, Ni(NO3)2·6H2O, NiSO4·6H2O, and NiCl6.
[0094] In some embodiments of the present invention, the buffer is selected from at least one of NH3·H2O and NH4HCO3.
[0095] In some embodiments of the present invention, the mixed solution 1 further contains a complexing agent and a pH regulator.
[0096] In some embodiments of the present invention, the molar ratio of perovskite precursor: complexing agent is 1:(1-1.2); in some embodiments of the present invention, the molar ratio of perovskite precursor: complexing agent can be any value of 1:1, 1:1.1, 1:1.12, 1:1.15, 1:1.17, 1:1.2 or a range formed by any two of them.
[0097] In some embodiments of the present invention, the complexing agent is selected from at least one of ethylenediaminetetraacetic acid (EDTA), citric acid, and ethylene glycol.
[0098] In some embodiments of the present invention, the molar ratio of perovskite precursor: pH adjuster is 1:(1.3-1.7); in some embodiments of the present invention, the molar ratio of perovskite precursor: pH adjuster can be any value of 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7 or a range formed by any two of them.
[0099] In some embodiments of the present invention, the pH adjuster is selected from at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, ammonia water, ammonia monohydrate, and ammonium bicarbonate.
[0100] In some embodiments of the present invention, the mixed solution 2 also contains a precipitant, and the molar ratio of the spinel-like precursor to the precipitant is 1:(1-1.5); in some embodiments of the present invention, the molar ratio of the spinel-like precursor to the precipitant can be any value of 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5 or a range formed by any two of them.
[0101] In some embodiments of the present invention, the precipitant is at least one of urea (CO(NH2)2), NH3·H2O, NH4HCO3, KOH, and K2CO3.
[0102] In some embodiments of the present invention, the molar ratio of the perovskite dry gel to the buffer is (3.2-4):1; in some embodiments of the present invention, the molar ratio of the perovskite dry gel to the buffer may be any one of 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4:1 or a range formed by any two of them.
[0103] In some embodiments of the present invention, the pH of the mixed solution 1 is 7.5-8; in some embodiments of the present invention, the pH of the mixed solution 1 can be any value of 7.5, 7.6, 7.7, 7.8, 7.9, 8 or a range formed by any two of them.
[0104] In some embodiments of the present invention, the pH of the mixed solution 2 is 7.5-8; in some embodiments of the present invention, the pH of the mixed solution 2 can be any value of 7.5, 7.6, 7.7, 7.8, 7.9, 8 or a range formed by any two of them. The precipitant in the mixed solution 2 can play a role in adjusting the pH.
[0105] In some embodiments of the present invention, the present invention further provides a cathode powder, which is prepared by the above-mentioned cathode powder preparation method; the cathode powder contains spinel-like and perovskite-like; the spinel-like is coated on the surface of the perovskite-like.
[0106] In some embodiments of the present invention, the specific surface area of the cathode powder is 4 to 8 m 2 / g.
[0107] In some embodiments of the present invention, the cathode powder D 50 The particle size is 0.62-0.74μm.
[0108] In some embodiments of the present invention, the cathode powder D 90 The particle size is 1.3-1.6μm.
[0109] In some embodiments of the present invention, the conductivity of the cathode powder is greater than 5S / cm.
[0110] In some embodiments of the present invention, the polarization impedance value of the cathode powder measured at 780°C is less than 0.96Ω·cm 2 .
[0111] In some embodiments of the present invention, the surface exchange coefficient of the cathode powder measured at 700°C is 7.11×10 -5 ~8.73×10 -5 cm / s.
[0112] In some embodiments of the present invention, the bulk oxygen chemical diffusion coefficient of the cathode powder measured at 600°C is 1.61×10 -3 ~2.13×10 -3 cm / s.
[0113] In some embodiments of the present invention, the present invention provides a solid oxide fuel cell, including a cathode, wherein the cathode contains the cathode powder mentioned above.
[0114] The specific implementation of the present invention is further described in detail below in conjunction with specific embodiments:
[0115] Example 1
[0116] This example provides a method for preparing cathode powder, comprising the following steps:
[0117] S1: Solution preparation and homogenization:
[0118] La(NO3)3 and Fe3(NO3)2·9H2O metal salt solutions were prepared into La3Fe2O7 type perovskite structure precursor solution in a stoichiometric ratio of 9:2, the solvents of La(NO3)3 metal salt solution and Fe3(NO3)2·9H2O metal salt solution were both water, and the concentrations were both 1 mol / L; La3Fe2O7 type perovskite structure precursor, complexing agent (i.e. citric acid), pH regulator (i.e. NaOH) were prepared into mixed solution 1 in a molar ratio of 1:1.1:1.5, and the pH of mixed solution 1 was 7.5;
[0119] The Mn(NO3)2 and Co(NO3)3·9H2O metal salt solutions are prepared into a MnCo2O4 spinel precursor solution in a stoichiometric ratio of 1:2, the solvent of the Mn(NO3)2 metal salt solution is water, and the concentration is 0.5 mol / L; the solvent of the Co(NO3)3·9H2O metal salt solution is water, and the concentration is 1 mol / L; the spinel precursor and the precipitant (i.e., urea, CO(NH2)2) are prepared into a mixed solution II in a molar ratio of 1:1.3, and the pH of the mixed solution II is adjusted to 7.5 using a pH regulator to obtain a mixed solution II;
[0120] Then, the mixed solution 1 and the mixed solution 2 were homogenized respectively, with a pressure of 220 MPa, a cycle number of 2 times, and a temperature of 35°C.
[0121] S2: Ultrasonic atomization treatment: The mixed solution 1 and the mixed solution 2 after the homogenization treatment in step S1 are subjected to ultrasonic atomization treatment in ultrasonic atomizer 1 and ultrasonic atomizer 2 respectively, with an ultrasonic frequency of 1.8 MHz and an atomization rate of 1.5 mL / min to obtain mixed aerosol 1 and mixed aerosol 2.
[0122] S3: Spray drying treatment: The mixed aerosol 1 and the mixed aerosol 2 are respectively introduced into the drying chamber 1 and the drying chamber 2 through the nitrogen carrier gas in the conduit for drying treatment. The spray drying time is 35 minutes, and the drying treatment temperature (i.e., the drying temperature T1 in the drying chamber 1 and the drying temperature T4 in the drying chamber 2) is 150°C.
[0123] S4: Thermal decomposition: The two dried mists obtained in step S3 are respectively introduced into thermal decomposition chamber 1 and thermal decomposition chamber 2 for thermal decomposition, wherein the thermal decomposition temperature T2 in thermal decomposition chamber 1 is 1300°C, and the time t2 is 90 min; the thermal decomposition temperature T5 in thermal decomposition chamber 2 is 1100°C, and the time t5 is 140 min. The two dried mists are thermally decomposed under a nitrogen atmosphere to form dry gel 1 (perovskite-like dry gel) and dry gel 2 (spinel-like dry gel).
[0124] S5: Coprecipitation treatment:
[0125] S5.1: First, the dry gel obtained in step S4 is brought into the sintering chamber by a nitrogen carrier gas via a syringe pump;
[0126] S5.2: Then, NH3·H2O buffer is pumped in for coating, with a gas flow rate of 15 mL / min and a coating time of 35 min, until the buffer is completely coated on the surface of the dry gel.
[0127] S5.3: Finally, the dry gel 2 obtained in step S4 is introduced, and the gas flow rate is 15 mL / min; then the temperature is slowly increased to 500°C (i.e., sintering temperature) at a heating rate of 8°C / min, and then kept warm for 3.5 hours to obtain the cathode powder in this example, i.e., the spinel-coated perovskite-like powder material.
[0128] The molar ratio of the perovskite-like xerogel to the buffer is 3.5:1, and the molar ratio of the perovskite-like xerogel to the spinel-like xerogel is 1:5.
[0129] The cathode powder prepared in this example is a La3Fe2O7 type perovskite material coated with a MnCo2O4 type spinel material.
[0130] Embodiments 2 to 5
[0131] The preparation method of the cathode powder in Examples 2 to 5 is different from that in Example 1 only in that the molar ratios of the La3Fe2O7-type perovskite structure precursor, the complexing agent and the pH regulator in the mixed solution 1 are different, as shown in Table 1.
[0132] Embodiment 6-7
[0133] The preparation method of the cathode powder in Examples 6 to 7 is different from that in Example 1 only in that the molar ratio of the spinel-like precursor and the precipitant in the second mixed solution is different, as shown in Table 1.
[0134] Embodiments 8 to 9
[0135] The preparation method of the cathode powder in Examples 8 to 9 is different from that in Example 1 only in that the molar ratio of the perovskite-like dry gel (i.e., dry gel 1) to the buffer in step S5 is different, as shown in Table 1.
[0136] Embodiments 10 to 13
[0137] The preparation method of the cathode powder in Examples 10 to 13 is different from that in Example 1 only in that the molar ratio of the perovskite-like dry gel (i.e., dry gel 1) to the spinel-like dry gel (i.e., dry gel 2) in step S5 is different, as shown in Table 1.
[0138] Comparative Examples 1-2
[0139] The preparation method of the cathode powder in Comparative Examples 1 to 2 is different from that in Example 1 only in that the molar ratio of the perovskite-like dry gel (i.e., dry gel 1) to the spinel-like dry gel (i.e., dry gel 2) in step S5 is different, as shown in Table 1.
[0140] Table 1 Dosage ratio of the preparation method in Examples 1 to 13 and Comparative Examples 1 to 2
[0141]
[0142] Embodiments 14 to 15
[0143] The preparation method of the cathode powder in Examples 14 to 15 is different from that in Example 1 only in that the homogenization pressure in step S1 is different, as shown in Table 2.
[0144] Embodiments 16 to 17
[0145] The preparation method of the cathode powder in Examples 16 to 17 is different from that in Example 1 only in that the homogenization temperature in step S1 is different, as shown in Table 2.
[0146] Examples 18 to 21
[0147] The method for preparing cathode powder in Examples 18 to 21 is different from that in Example 1 only in that the ultrasonic frequency in step S2 is different, as shown in Table 2.
[0148] Embodiments 22 to 25
[0149] The method for preparing cathode powder in Examples 22 to 25 is different from that in Example 1 only in that the atomization rate in step S2 is different, as shown in Table 2.
[0150] Embodiments 26 to 27
[0151] The preparation method of the cathode powder in Examples 26 to 27 is different from that in Example 1 only in that the drying time in step S3 is different, as shown in Table 2.
[0152] Embodiments 28 to 29
[0153] The preparation method of the cathode powder in Examples 28 to 29 is different from that in Example 1 only in that the drying temperature in step S3 is different, as shown in Table 2.
[0154] Comparative Examples 3-4
[0155] The preparation method of the cathode powder in Comparative Examples 3 to 4 is different from that in Example 1 only in that the ultrasonic frequency in step S2 is different, as shown in Table 2.
[0156] Comparative Examples 5-6
[0157] The preparation method of the cathode powder in Comparative Examples 5 to 6 is different from that in Example 1 only in that the atomization rate in step S2 is different, as shown in Table 2.
[0158] Table 2 Process parameters of the preparation methods in Examples 14 to 29 and Comparative Examples 3 to 6
[0159]
[0160]
[0161] Embodiments 30 to 33
[0162] The preparation method of the cathode powder in Examples 30 to 33 is different from that in Example 1 only in that the thermal decomposition temperature T2 in the thermal decomposition chamber 1 in step S4 is different, as shown in Table 3.
[0163] Embodiments 34 to 37
[0164] The preparation method of the cathode powder in Examples 34 to 37 is different from that in Example 1 only in that the pyrolysis time t2 in the pyrolysis chamber 1 in step S4 is different, as shown in Table 3.
[0165] Embodiments 38 to 41
[0166] The preparation method of the cathode powder in Examples 38 to 41 is different from that in Example 1 only in that the thermal decomposition temperature T5 in the thermal decomposition chamber 2 in step S4 is different, as shown in Table 3.
[0167] Embodiments 42 to 45
[0168] The preparation method of the cathode powder in Examples 42 to 45 is different from that in Example 1 only in that the pyrolysis time t5 in the pyrolysis chamber 2 in step S4 is different, as shown in Table 3.
[0169] Embodiments 46 to 49
[0170] The preparation method of the cathode powder in Examples 46 to 49 is different from that in Example 1 only in that the coating time in step S5.2 is different, as shown in Table 3.
[0171] Embodiments 50 to 53
[0172] The method for preparing cathode powder in Examples 50 to 53 is different from that in Example 1 only in that the heating rate in step S5.3 is different, as shown in Table 3.
[0173] Embodiments 54 to 57
[0174] The preparation method of the cathode powder in Examples 54 to 57 is different from that in Example 1 only in that the sintering temperature in step S5.3 is different, as shown in Table 3.
[0175] Embodiments 58 to 61
[0176] The method for preparing cathode powder in Examples 58 to 61 is different from that in Example 1 only in that the insulation time in step S5.3 is different, as shown in Table 3.
[0177] Comparative Examples 7 to 8
[0178] The preparation method of the cathode powder in Comparative Examples 7 to 8 is different from that in Example 1 only in that the thermal decomposition temperature T2 in the thermal decomposition chamber 1 in step S4 is different, as shown in Table 3.
[0179] Comparative Examples 9 to 10
[0180] The preparation method of the cathode powder in Comparative Examples 9 to 10 is different from that in Example 1 only in that the pyrolysis time t2 in the pyrolysis chamber 1 in step S4 is different, as shown in Table 3.
[0181] Comparative Examples 11-12
[0182] The preparation method of the cathode powder in Comparative Examples 11 to 12 is different from that in Example 1 only in that the thermal decomposition temperature T5 in the thermal decomposition chamber 2 in step S4 is different, as shown in Table 3.
[0183] Comparative Examples 13-14
[0184] The preparation method of the cathode powder in Comparative Examples 13 to 14 is different from that in Example 1 only in that the pyrolysis time t5 in the pyrolysis chamber 2 in step S4 is different, as shown in Table 3.
[0185] Comparative Examples 15 to 17
[0186] The preparation methods of cathode powders in Comparative Examples 15 to 17 differ from those in Example 1 only in that the coating time in step S5.2 is different, as shown in Table 3.
[0187] Comparative Examples 18-19
[0188] The preparation method of the cathode powder in Comparative Examples 18 to 19 is different from that in Example 1 only in that the heating rate in step S5.3 is different, as shown in Table 3.
[0189] Comparative Examples 20-21
[0190] The preparation method of the cathode powder in Comparative Examples 20-21 is different from that in Example 1 only in that the sintering temperature in step S5.3 is different, as shown in Table 3.
[0191] Comparative Examples 22-23
[0192] The preparation method of the cathode powder in Comparative Examples 22 to 23 is different from that in Example 1 only in that the insulation time in step S5.3 is different, as shown in Table 3.
[0193] Comparative Example 24
[0194] This example provides a method for preparing cathode powder. The difference between this example and Example 1 is that this example does not use a double channel. The preparation method in this example includes the following steps:
[0195] S1: Solution preparation and homogenization:
[0196] La(NO3)3 and Fe3(NO3)2·9H2O metal salt solutions were prepared into La3Fe2O7 type perovskite structure precursor solution in a stoichiometric ratio of 9:2, the solvents of La(NO3)3 metal salt solution and Fe3(NO3)2·9H2O metal salt solution were both water, and the concentrations were both 1 mol / L; La3Fe2O7 type perovskite structure precursor, complexing agent (i.e. citric acid), pH regulator (i.e. NaOH) were prepared into mixed solution 1 in a molar ratio of 1:1.1:1.5, and the pH of mixed solution 1 was 7.5;
[0197] Mn(NO3)2 and Co(NO3)3·9H2O metal salt solutions are prepared into a MnCo2O4 spinel precursor solution at a stoichiometric ratio of 1:2, the solvent of the Mn(NO3)2 metal salt solution is water, and the concentration is 0.5 mol / L; the solvent of the Co(NO3)3·9H2O metal salt solution is water, and the concentration is 1 mol / L, the spinel precursor and the precipitant (i.e., urea, CO(NH2)2) are prepared into a mixed solution at a molar ratio of 1:1.3, and then the pH of the mixed solution is adjusted to 7.5 with a pH adjuster (i.e., NaOH) to obtain a mixed solution II;
[0198] Then, the mixed solution 1 and the mixed solution 2 were mixed and homogenized at a pressure of 220 MPa, a cycle number of 2 times, and a temperature of 35°C.
[0199] S2: Ultrasonic atomization treatment: The mixed liquid after the homogenization treatment in step S1 is subjected to ultrasonic atomization treatment in an ultrasonic atomizer, the ultrasonic frequency is 1.8 MHz; the atomization rate is 1.5 mL / min, and a mixed aerosol is obtained.
[0200] S3: Spray drying: The mixed aerosol is passed into a drying chamber through the nitrogen carrier gas in a conduit for drying. The spray drying time is 35 minutes and the drying temperature is 150°C.
[0201] S4: Thermal decomposition: The dried mixed mist obtained in step S3 is introduced into a thermal decomposition chamber for thermal decomposition, wherein the thermal decomposition temperature T2 in the thermal decomposition chamber is 1300° C. and the time t2 is 90 min; the dried mixed mist is thermally decomposed in a nitrogen atmosphere to form a mixed dry gel.
[0202] S5: Coprecipitation treatment:
[0203] S5.1: First, the mixed xerogel obtained in step S4 is brought into the sintering chamber by a nitrogen carrier gas via a syringe pump;
[0204] S5.2: Then, NH3·H2O buffer was pumped in for coating, with a gas flow rate of 15 mL / min and a coating time of 35 min.
[0205] S5.3: Then slowly increase the temperature to 500°C (ie, sintering temperature) at a heating rate of 8°C / min, and then keep the temperature for 3.5 hours to obtain the cathode powder in this example.
[0206] The molar ratio of the perovskite-like xerogel to the buffer is 3.5:1, and the molar ratio of the perovskite-like xerogel to the spinel-like xerogel is 1:5.
[0207] Comparative Example 25
[0208] This example provides a method for preparing cathode powder, which differs from Example 1 in that ultrasonic atomization treatment is not used; the preparation method in this example includes the following steps:
[0209] S1: Solution preparation and homogenization:
[0210] La(NO3)3 and Fe3(NO3)2·9H2O metal salt solutions were prepared into La3Fe2O7 type perovskite structure precursor solution in a stoichiometric ratio of 9:2, the solvents of La(NO3)3 metal salt solution and Fe3(NO3)2·9H2O metal salt solution were both water, and the concentrations were both 1 mol / L; La3Fe2O7 type perovskite structure precursor, complexing agent (i.e. citric acid), pH regulator (i.e. NaOH) were prepared into mixed solution 1 in a molar ratio of 1:1.1:1.5, and the pH of mixed solution 1 was 7.5;
[0211] The Mn(NO3)2 and Co(NO3)3·9H2O metal salt solutions were prepared into a MnCo2O4 spinel precursor solution at a stoichiometric ratio of 1:2. The solvent of the Mn(NO3)2 metal salt solution was water with a concentration of 0.5 mol / L; the solvent of the Co(NO3)3·9H2O metal salt solution was water with a concentration of 1 mol / L. The spinel precursor and the precipitant (i.e., urea, CO(NH2)2) were prepared into a mixed solution at a molar ratio of 1:1.3, and then the pH of the mixed solution was adjusted to 7.5 with a pH adjuster (i.e., NaOH) to obtain a mixed solution II;
[0212] Then, the mixed solution 1 and the mixed solution 2 were homogenized respectively, with a pressure of 220 MPa, a cycle number of 2 times, and a temperature of 35°C.
[0213] S2: Drying treatment: The mixed liquid 1 and the mixed liquid 2 are respectively passed through the nitrogen carrier gas in the conduit into the drying chamber 1 and the drying chamber 2 for drying treatment. The drying treatment time is 35 minutes, and the drying treatment temperature (i.e., the drying temperature T1 in the drying chamber 1 and the drying temperature T4 in the drying chamber 2) is 150°C.
[0214] S3: Thermal decomposition: The two dried mixtures obtained in step S2 are respectively introduced into thermal decomposition chamber 1 and thermal decomposition chamber 2 for thermal decomposition, wherein the thermal decomposition temperature T2 in thermal decomposition chamber 1 is 1300°C, and the time t2 is 90 min; the thermal decomposition temperature T5 in thermal decomposition chamber 2 is 1100°C, and the time t5 is 140 min. The two dried mixtures are thermally decomposed under a nitrogen atmosphere to form dry gel 1 (perovskite-like dry gel) and dry gel 2 (spinel-like dry gel).
[0215] S4: Coprecipitation treatment:
[0216] S4.1: First, the dry gel obtained in step S3 is brought into the sintering chamber by a nitrogen carrier gas via a syringe pump;
[0217] S4.2: Then pump in NH3·H2O buffer with a gas flow rate of 15 mL / min and a coating time of 35 min until the buffer is completely coated on the surface of the dry gel.
[0218] S4.3: Finally, the dry gel 2 obtained in step S3 is introduced, and the gas flow rate is 15 mL / min; then the temperature is slowly increased to 500°C (i.e., sintering temperature) at a heating rate of 8°C / min, and then kept warm for 3.5 hours to obtain the cathode powder in this example, i.e., the spinel-coated perovskite-like powder material.
[0219] The molar ratio of the perovskite-like xerogel to the buffer is 3.5:1, and the molar ratio of the perovskite-like xerogel to the spinel-like xerogel is 1:5.
[0220] Table 3 Process parameters of the preparation methods in Examples 30 to 61 and Comparative Examples 7 to 23
[0221]
[0222]
[0223] Performance Testing:
[0224] The specific surface area, particle size distribution, electrical conductivity, catalytic activity and reaction activity of the cathode powders prepared by the preparation methods in Examples 1 to 61 and Comparative Examples 1 to 25 were tested respectively. The specific test methods are as follows:
[0225] a) Powder specific surface area:
[0226] Test method: The present invention uses a specific surface area analyzer to test the specific surface area of the above-synthesized cathode powder;
[0227] Standard: 4-8m 2 / g;
[0228] b) Particle size distribution of powder D 50 , D 90 :
[0229] Test method: Use a laser particle size analyzer to test the particle size distribution of the powder, use deionized water as a solvent, and the shading degree is required to be 14% to 18%;
[0230] Standard: D 50 The most suitable range is 0.62-0.74μm, D 90 The most suitable range is 1.3-1.6μm.
[0231] c) Conductivity test
[0232] Test method: Place the prepared cathode powder into a 25mm*5mm strip mold and press it. Sinter the pressed strip in 5% H2 / Ar (i.e., the volume of H2 is 5% of the volume of Ar) to obtain a test sample. Tie silver wires between the two sides of the sample at a distance of L. Evenly apply silver conductive glue on the cross-sections at both ends and bond silver wires as collectors. Use a counting multimeter and a DC power supply to test the conductivity of the sample at 780°C. The conductivity calculation formula for the strip sample is:
[0233] σ=VS / IL
[0234] S is the cross-sectional area of the sample, I is the current applied, and V is the voltage across a certain length L.
[0235] Standard:>5S / cm;
[0236] d) Catalytic activity of powder
[0237] Test method: pinene alcohol and ethyl cellulose (in a mass ratio of 9:1) are mixed and stirred into a colloid to prepare an organic synthetic agent; the organic synthetic agent is fully ground and mixed with the cathode powder prepared by the present invention to form a cathode slurry (the mass ratio of the organic synthetic agent to the cathode powder is 9:11), and screen-printed on both sides of a 240μm LSGM electrolyte.
[0238] Sintered at 850℃ for 5h under 5% H2 / Ar conditions, and then connected to both sides of the symmetrical battery with silver wires for current collection. n+1 B n O 3n+1 &CD2O4||GDC||LSGM||GDC||A n+1 B n O 3n+1 &CD2O4 structure symmetrical battery, in which A n+ 1B n O 3n+1 &CD2O4 is the cathode powder prepared in the present invention, GDC is gadolinium-doped cerium oxide (Gd 0.1 Ce 0.9 O 1.95 ), LSGM electrolyte is lanthanum strontium gallium magnesium oxide (La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 2.05 ). In the dry H2 power generation mode, the temperature was raised to 780°C at a rate of 30°C / h, and the activation polarization impedance value of the powder was tested using an electrochemical impedance spectroscopy instrument.
[0239] Compliance standard: Polarization impedance value is required to be less than 0.96Ω·cm 2 @780℃.
[0240] e) Reactivity of powder
[0241] Test method: prepare cylindrical tablets using the Vander Pauw method for conductivity relaxation test; place the cathode powder prepared by the present invention in a tablet press and press at a pressure of 0.5 MPa for 3 minutes to prepare a dense tablet with a thickness of 1 mm; polish with sandpaper of different mesh sizes; evenly coat the polished surface with a mixed slurry of gold powder and carbon powder; heat from room temperature to 750°C at a heating rate of 5°C / min for 1 hour; then test and record the oxygen partial pressure by ST Lab, SiOS-200C at 700 / 600°C, a perturbation current of 100 microamperes, and a pressure of 21.28 / 10.13Kpa respectively; fit and output the bulk oxygen chemical diffusion coefficient and the surface exchange coefficient by the ECR tool.
[0242] Compliance Standards:
[0243] Surface exchange coefficient: 7.11×10 -5 ~8.73×10 -5 cm / s@700℃;
[0244] Bulk oxygen chemical diffusion coefficient: 1.61×10 -3 ~2.13×10 -3 cm / s@600℃;
[0245] The performance data of the cathode powders prepared by the preparation methods in Examples 1 to 13 and Comparative Examples 1 to 2 measured according to the above test method are shown in Table 4 below; the performance data of the cathode powders prepared by the preparation methods in Examples 14 to 61 and Comparative Examples 3 to 25 are shown in Table 5 below.
[0246] Table 4 Performance data of cathode powders in Examples 1 to 13 and Comparative Examples 1 to 2
[0247]
[0248] As can be seen from Table 4, by comparing Examples 1 to 13 with Comparative Examples 1 to 2, when the molar ratio of dry gel 1 to dry gel 2 is lower than 1:4.5 (for example, the molar ratio of the two in Comparative Example 1 is 1:4), the coating layer is thinner when dry gel 1 and dry gel 2 are co-precipitated, resulting in the cathode powder being too fine in particle size, the specific surface area being correspondingly increased, and the conductivity, catalytic activity, surface oxygen exchange coefficient, and bulk chemical diffusion coefficient of the cathode powder being reduced; when the molar ratio of dry gel 1 to dry gel 2 is higher than 1:6.5 (for example, the molar ratio of the two in Comparative Example 2 is 1:7), the coating layer particle agglomerates are too large when dry gel 1 and dry gel 2 are co-precipitated, resulting in the cathode powder being too coarse in particle size, the specific surface area being correspondingly reduced, the conductivity, surface oxygen exchange coefficient, and bulk chemical diffusion coefficient of the cathode powder being reduced, the polarization impedance being increased, and the catalytic activity being reduced.
[0249] Table 5 Performance data of cathode powders in Examples 14 to 61 and Comparative Examples 3 to 25
[0250]
[0251]
[0252] It can be seen from Table 5 that by comparing Example 1, Examples 18-21 and Comparative Examples 3-4, when the ultrasonic frequency is too low, the particle size of the cathode powder is larger and the distribution range is wider, so the specific surface area, conductivity and catalytic activity of the cathode powder are reduced, and the surface oxygen exchange coefficient and the bulk chemical diffusion coefficient are reduced accordingly; when the ultrasonic frequency is too high, the particle size of the cathode powder is too fine and the specific surface area is large, so the cathode powder is not sufficiently coated after co-precipitation treatment, and the catalytic activity and conductivity of the cathode powder are reduced accordingly, and the surface oxygen exchange coefficient and the bulk chemical diffusion coefficient are reduced accordingly.
[0253] By comparing Example 1, Examples 22-25 and Comparative Examples 5-6, it can be seen that when the ultrasonic atomization rate is too fast, the droplet size is extremely small due to high-frequency vibration and cavitation, the particle size distribution of the synthesized cathode powder is wide, and the conductivity is reduced. When the ultrasonic atomization rate is too slow, the atomization is insufficient, and the D of the synthesized cathode powder is 50 , D 90 The particle sizes increased and the gaps widened.
[0254] By comparing Examples 1, 30-37, 38-45 with Comparative Examples 7, 9, 11, and 13, it can be seen that when the thermal decomposition temperature is too low or the holding time is too short, due to insufficient decomposition of the precursor, the particle size of the synthesized cathode powder is large, so the specific surface area, electrical conductivity and catalytic activity of the cathode powder are significantly reduced, and the surface oxygen exchange coefficient and the bulk chemical diffusion coefficient are correspondingly reduced; by comparing Examples 1, 30-37, 38-45 with Comparative Examples 8, 10, 12, and 14, it can be seen that when the thermal decomposition temperature is too high, it has no effect on the particle size, specific surface area and catalytic activity of the cathode powder; but gas will be generated, the pressure will rise suddenly, and there is a risk of excessive pressure and easy explosion.
[0255] By comparing Examples 1, 46-49 with Comparative Examples 15 and 16, it can be seen that when the holding time is too short, the particle size of the cathode powder synthesized by the coprecipitation is large and the particle size distribution is too wide due to insufficient coating of the perovskite surface buffer, so the specific surface area, conductivity and catalytic activity of the cathode powder are significantly reduced, and the surface oxygen exchange coefficient and bulk chemical diffusion coefficient are correspondingly reduced. The holding time of Comparative Example 17 is too long, which has little effect on the performance, but seriously affects the production efficiency.
[0256] By comparing Examples 1, 50-53 and Comparative Example 18, it can be seen that the heating rate is too slow, the powder cannot be fully precipitated and crystallized, the powder particle size is too fine, and the specific surface area is too large, resulting in reduced electrical conductivity and catalytic activity of the powder, and corresponding reductions in the surface oxygen exchange coefficient and the bulk chemical diffusion coefficient.
[0257] By comparing Examples 1, 50-53 and Comparative Example 19, it can be seen that when the heating rate is too fast, the crystallization rate of the cathode powder increases sharply, the particle size distribution of the cathode powder becomes wider, and the specific surface area is significantly reduced, resulting in reduced electrical conductivity and catalytic activity of the cathode powder, and corresponding reductions in the surface oxygen exchange coefficient and the bulk chemical diffusion coefficient.
[0258] By comparing Examples 1, 54-57 and Comparative Example 20, it can be seen that if the precipitation temperature is too high, the D of the cathode powder will be too large due to excessive grain growth. 50 and D 90 By comparing Examples 1, 54-57 and Comparative Example 21, it can be seen that when the precipitation temperature is too low, the precipitation and crystallization of the spinel-like perovskite surface is insufficient, D 50 and D 90 Both increase and the specific surface area decreases.
[0259] By comparing Examples 1, 58-61 and Comparative Example 22, it can be seen that the heat preservation time during the precipitation treatment is too short, the cathode powder crystallization is insufficient, and the crystals cannot grow, resulting in D 50 and D 90 By comparing Examples 1, 58-61 and Comparative Example 23, it can be seen that: the precipitation temperature is too long, the cathode powder is excessively crystallized, and D 50 and D 90 Both increase and the difference increases, and the specific surface area of the cathode powder increases accordingly, resulting in performance that does not meet the requirements.
[0260] By comparing Example 1 and Comparative Example 24, it can be seen that under the same single-channel preparation process, the D 50 and D 90 The gap has increased significantly, the conductivity and catalytic activity of the cathode powder are seriously below the standard, and the surface oxygen exchange coefficient and bulk chemical diffusion coefficient are reduced accordingly;
[0261] By comparing Example 1 with Comparative Example 25, it can be seen that when the preparation process without spray drying is used, the D 50 and D 90 The conductivity and catalytic activity of the cathode powder were seriously below the standard, and the surface oxygen exchange coefficient and bulk chemical diffusion coefficient were correspondingly reduced.
[0262] In summary, the present invention introduces ultrasonic spray and homogenization treatment processes, combined with a dual-channel design, and performs ultrasonic, spray drying and thermal decomposition treatments on a perovskite-like precursor solution and a spinel-like precursor solution, respectively, to achieve the preparation of xerogels with different particle sizes and specific surface areas, and then performs coprecipitation treatment in a sintering chamber according to optimal process parameters and processes to form a cathode powder with a coated structure having uniform particle size and high purity. The cathode powder prepared by the present invention exhibits higher electrical conductivity, ionic conductivity, and excellent catalytic activity and reaction activity.
[0263] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A method for preparing cathode powder, characterized in that: The following steps are involved: Step 1: homogenizing, ultrasonically atomizing, and drying the mixed solution 1 and the mixed solution 2 in sequence to obtain a mixed aerosol 1 and a mixed aerosol 2; Step 2: thermally decomposing the mixed aerosol 1 and the mixed aerosol 2 to obtain a perovskite-like xerogel and a spinel-like xerogel, respectively; Step 3: sequentially coating the surface of the perovskite-like dry gel with a buffer and a spinel-like dry gel, and then sintering to obtain the cathode powder; The first mixed solution contains a perovskite-like precursor; the second mixed solution contains a spinel-like precursor; The molar ratio of the perovskite-like dry gel to the spinel-like dry gel is 1:(4.5-6.5).
2. The method for preparing cathode powder according to claim 1, characterized in that: The ultrasonic frequency in the ultrasonic atomization step is 1.5 to 2 Hz; and / or, the atomization rate in the ultrasonic atomization step is 1 to 2 mL / min; And / or, the thermal decomposition temperature of the mixed aerosol is 1200-1400°C; And / or, the thermal decomposition time of the mixed aerosol is 80-100 min; and / or, the thermal decomposition temperature of the mixed aerosol 2 is 1000-1200° C.; and / or, the thermal decomposition time of the mixed aerosol 2 is 110-160 min; and / or, the time required for coating the buffer on the surface of the perovskite-like xerogel is not less than 30 minutes; And / or, the heating rate of the sintering step is 5 to 10°C / min; And / or, the sintering temperature of the sintering step is 400-600°C; And / or, the holding time of the sintering step is 3 to 4 hours; And / or, the drying temperature is 100-200°C; And / or, the drying time is 30-40 min; And / or, the pressure of the homogenization step is 200-250 MPa; And / or, the temperature of the homogenization step is 30-40°C.
3. The method for preparing cathode powder according to claim 1, characterized in that: The step 3 is: passing the gas containing the buffer into the gas containing the perovskite-like dry gel so that the buffer is coated on the surface of the perovskite-like dry gel; then passing the gas containing the spinel-like dry gel, and then sintering.
4. The method for preparing cathode powder according to claim 3, characterized in that: The flow rate of the gas containing the buffer is <20 mL / min; And / or, the flow rate of the gas containing the spinel-like xerogel is <20 mL / min.
5. The method for preparing cathode powder according to claim 1, characterized in that: The perovskite-like n+ 1B n O 3n+1 ; n is an integer of 1 to 4; A is selected from rare earth metals; B is selected from transition metals; And / or, the spinel-like material is CD2O4; C and D are both transition metals; And / or, the buffer is selected from at least one of NH3·H2O and NH4HCO3.
6. The method for preparing cathode powder according to claim 1, characterized in that: The mixed solution 1 also contains a complexing agent and a pH regulator, and the molar ratio of the perovskite precursor: the complexing agent: the pH regulator is 1: (1-1.2): (1.3-1.7); And / or, the second mixed solution further contains a precipitant, and the molar ratio of the spinel-like precursor to the precipitant is 1:(1-1.5); And / or, the molar ratio of the perovskite-like xerogel to the buffer is (3.2-4):
1.
7. The method for preparing cathode powder according to claim 1, characterized in that: The pH of the mixed solution 1 and / or the mixed solution 2 is 7.5-8.
8. A cathode powder, characterized in that: The cathode powder is prepared by the preparation method according to any one of claims 1 to 7; the cathode powder contains spinel-like and perovskite-like; the spinel-like is coated on the surface of the perovskite-like.
9. The cathode powder according to claim 8, characterized in that: The cathode powder has at least one of the following characteristics: (a) The specific surface area of the cathode powder is 4 to 8 m 2 / g; (b) D of the cathode powder 50 Particle size is 0.62-0.74 μm; (c) D of the cathode powder 90 Particle size is 1.3-1.6 μm; (d) the conductivity of the cathode powder is greater than 5S / cm; (e) The polarization impedance value of the cathode powder measured at 780°C is less than 0.96Ω·cm 2 ; (f) The surface exchange coefficient of the cathode powder measured at 700°C is 7.11×10 -5 ~8.73×10 -5 cm / s; (g) The bulk oxygen chemical diffusion coefficient of the cathode powder measured at 600°C is 1.61×10 -3 ~2.13×10 -3 cm / s.
10. A solid oxide fuel cell, characterized in that: It comprises a cathode, wherein the cathode contains the cathode powder according to claim 8 or 9.
Citation Information
Patent Citations
Coating-structure composite conducting ceramic material and cathode contact layer, and their preparation method
CN103427092A
Cathode material and preparation method and application thereof
CN116435529A
Preparation method of composite coating with coating structure and composite coating
CN117080461A
Integrated preparation method for coating and current collector of solid oxide fuel cell
CN117117230A
Method of preparation of homogeneous oxides of two or more elements in a fineley divided form and products obtained
GB1282307A